(untitled) (Scientific journal of the Fergana State University, 2025)
The article discusses the mechanics of the development of pedagogical culture and competence of future teachers of Physical Culture. It is also reported about teaching the content of the development of pedagogical culture and competence of future teachers of Physical Culture on a scientific basis, modernizing its organizational and technological foundations.